La enseñanza de las ciencias como espacio para la formación de valores democráticos: un análisis desde el enfoque de las cuestiones sociocientíficas (2026)
Contemporary approaches to science education emphasize the need to move beyond instruction focused solely on disciplinary content and toward educational processes aimed at fostering critical thinking, participation, and democratic values. In this context, this article analyzes the potential of science education as a space for the formation of democratic values, based on a reinterpretation of previous research that addresses socioscientific issues as a pedagogical strategy. The study adopts a qualitative and analytical approach through which the theoretical and methodological contributions of the base study are reviewed and reorganized in order to resignify them from an educational perspective centered on deliberation, dialogue, and informed decision-making. Science education is understood as a privileged setting for the discussion of socially relevant issues, where students can articulate scientific knowledge with ethical, social, and political reflections, thereby strengthening their development as citizens.